Crystal structure of Mo‐substituted lanthanum tungstate La5.4W1−yMoyO12−δ (0 ≤ y ≤ 0.2) studied by X‐ray and neutron diffraction. Issue 5 (6th September 2019) - Fantin, Andrea; Scherb, Tobias; Seeger, Janka; Schumacher, Gerhard; Gerhards, Uta; Ivanova, Mariya E.; Meulenberg, Wilhelm A.; Dittmeyer, Roland; Banhart, John
Abstract : This work describes in detail the crystal structure of Mo‐substituted lanthanum tungstates, determined through neutron diffraction and high‐resolution X‐ray diffraction as a function of temperature between T = 10 K and T = 298 K. Combined X‐ray and neutron‐diffraction refinements and electron‐probe micro‐analysis were employed to locate Mo atoms in the crystal structure of La5.4 W1− y Mo y O12−δ (0 ≤ y ≤ 0.2). Abstract : A determination of the detailed crystal structure of an Mo‐substituted lanthanum tungstate series, La6− x W1− y Mo y O12−δ (0 ≤ y ≤ 0.2, δ is the oxygen deficiency), is presented. Material of composition La5.4 W0.8 Mo0.2 O12−δ ( y = 0.2) produced by the citrate‐complexation route based on the Pechini method was investigated by high‐resolution X‐ray diffraction and neutron diffraction in the temperature range 10 ≤ T ≤ 298 K. The results are compared with a non‐substituted material La5.4 WO12−δ . A structural model established earlier for lanthanum tungstates and Re‐substituted lanthanum tungstates is confirmed, according to which the Wyckoff site shared by La and W is split with half site occupancies ( space group, 48 h site) and also accommodates Mo atoms. Substitution of W by up to 20 mol% Mo does not change the face‐centred cubic lattice: Mo atoms substitute W statistically on both 4 a and 48 h Wyckoff sites of the crystal structure, which is described by the space group. These results were obtained from the combination of the average neutron‐scattering length and average X‐ray scattering power procedures with electron‐probe micro‐analysis. The temperature dependence of bond lengths in dry and wet (D2 O) conditions shows that vacant oxygen sites are located on the 32 f Wyckoff sites also in Mo‐substituted lanthanum tungstates, and that the bond lengths between La on 4 b and O on 32 f increase with increasing p O2 and p D2 O, reflecting the filling of oxygen vacancies and the increase in coordination of La on 4 b .